Positivism and University Reform in Honduras During the Government of Marco Aurelio Soto (1876-1883) - Cardona Amaya, José Manuel (2023)
This paper exposes the university reform based on positivism led by the government of Marco Aurelio Soto (1876-1883) in Honduras. Its objective is to demonstrate how the reformers raised the positivist philosophy as an advance compared to the humanistic model that Honduran university previously had and how this current of thought was reflected in the Code of Public Instruction of 1882. Original sources of the time were used, through which it was possible to show the arguments used by the reformers to adopt the positivist model. It was concluded that the university reform promoted by the liberal reformers in Honduras failed and that the model faced reforms and readjustments in the years immediately following its imposition.